On Commonalities and Disparities: Collected Essays on German-Italian Scientific Networks (KULT_online, 2009)
Implicit in the title of this volume, published by Gian Rusconi and Hans Woller and available in German since 2006, is that both the parallels and the dissimilarities of German-Italian history since 1945 will be presented. A group of renowned authors – 23 in all – take on just this task, and offer up an admirable diversity of topics that covers the spectrum from the ending of the dictatorship and its legacy to the German reunification. The collection, released in Italy in 2005, is primarily meant to bring German readers up-to-date on Italian research, and is therefore a prime example of the German-Italian scientific network at its best. Unfortunately, developments during the 1960s and '70s are almost completely disregarded, as are considerations of the media and publicity.